Anti urolithiatic activity of Cyperus rotundus tubers: In silico, In vitro and In vivo approaches - Swathi Golla; Praveen Kumar Pasala; Suman Sura; Kavya Nainita; Deepika Katabathina (Universidade de São Paulo, 2023)
Abstract The present research evaluated the anti urolithic potential of Cyperus rotundus tubers extract using in silico, in vitro and in vivo techniques. In silicostudy was performed of Cyperus rotundus constituents and pathological protein oxalate oxidase (PDB Id: 2ETE). In vitrostudy, nucleation and aggregation assay involved for assessment of ethanol extract of Cyperus rotundus tuber (50-3000 µg/ml).In vivo studies involved that the Cyperus rotundusethanolic extract (100, 200 and 400 mg/kg B.wt.) wastreatedonsodium oxalate induced urolithiatic rats for seven days,evaluated kidney function by urine and serum biochemical analysis and statistical analysis performed usingGraphPad prism5 software.In silico results showedthat Cyperus rotundus constituents,Humulene epoxide, 4-Oxo-alpha-ylangene, Cubebol were exhibited better binding energyonoxalate oxidase.Ethanolic extract of Cyperus rotundustuber was exhibited nucleation, aggregation of calcium oxalate monohydrate crystals inhibition in dosedependent manner. Sodium oxalate treatment was triggered biochemical changesin the urine that have been substantially prevented by the ethanolic extract of Cyperus rotundus tuber. The current findings Cyperus rotundus anti urolithic activity due to antioxidant essential oils. The molecular docking results could be used to optimize lead and develop the appropriate urolithiasis treatment.